Evaluation of CT Scan Room Layout and Design for Optimization Radiology Service Delivery - Tri darmawan, Zulkifli; Auliawan, Arya; Normawati, Sitti; Musdalifah, Indah (Bantayang Omni Cendekia, 2025)
Background: The effectiveness of CT scan procedures is significantly influenced by the spatial design of radiology rooms. Inadequate room layouts can hinder workflow efficiency, reduce patient comfort, and compromise safety and regulatory compliance. Objective: This study aims to evaluate the layout of the CT scan room at Jaury Jusuf Putera Academic Hospital and propose improvements in accordance with national hospital design standards. Methods: A qualitative case study approach was employed, utilizing structured field observations to assess the functionality of seven designated spaces within the CT scan unit. Results: While five essential rooms were present, the absence of a patient toilet and a changing room highlighted partial non-compliance with applicable regulatory standards. Conclusion: It is recommended that hospital management revise the current spatial configuration to incorporate the missing support rooms. Such modifications are expected to enhance patient comfort, optimize workflow, and ensure greater adherence to national standards.